2015
DOI: 10.1002/anie.201506990
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐Light‐Catalyzed Direct Benzylic C(sp3)–H Amination Reaction by Cross‐Dehydrogenative Coupling

Abstract: A conceptually new and synthetically valuable cross-dehydrogenative benzylic C(sp(3))-H amination reaction is reported by visible-light photoredox catalysis. This protocol employs DCA (9,10-dicyanoanthracene) as a visible-light-absorbing photoredox catalyst and an amide as the nitrogen source without the need of either a transition metal or an external oxidant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(41 citation statements)
references
References 85 publications
(14 reference statements)
0
41
0
Order By: Relevance
“…Similar to the iminyl radical generation, the use of hydroxylamine derivatives has turned out to be very efficient [128,139]. The generation of amidyl radicals using organophotoredox catalysis was first reported by Pandey and Laha in 2015 (Scheme 30) [146]. They developed an intermolecular crossdehydrogenative benzylic C(sp 3 ) amination between the aryl substrates 30.1 and the amides 30.2 for the synthesis of the Weinreb amides 30.3 using DCA (OD5) as an organic dye.…”
Section: Amidyl Radical Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the iminyl radical generation, the use of hydroxylamine derivatives has turned out to be very efficient [128,139]. The generation of amidyl radicals using organophotoredox catalysis was first reported by Pandey and Laha in 2015 (Scheme 30) [146]. They developed an intermolecular crossdehydrogenative benzylic C(sp 3 ) amination between the aryl substrates 30.1 and the amides 30.2 for the synthesis of the Weinreb amides 30.3 using DCA (OD5) as an organic dye.…”
Section: Amidyl Radical Generationmentioning
confidence: 99%
“…Illustrative example for the photocatalytic oxidative generation of amidyl radicals from Weinreb amides: the cross-dehydrogenative benzylic C(sp 3 )-H amination reported by Pandey and Laha [146].…”
Section: Scheme 30mentioning
confidence: 99%
“…The mechanistic studies revealed that both visible light and catalyst were required for the CÀ H fluorination, while a non-metal radical CÀ H abstraction is involved in the rate-limiting step. In another report, Pandey and Laha demonstrated a direct amination of benzylic CH bond via visible-light-mediated oneelectron photoredox oxidation affording the corresponding mono-aminated products in good to excellent yields (Scheme 48) [65] The cross-dehydrogenative coupling proposedly involved the benzylic CÀ H radical formation via hydrogen atom transfer to an aminyl radical followed by one electron oxidation of benzylic radical to form benzylcarbocation. The aminyl radical was generated from amine by one-electron oxidation in the presence of 9,10-dicyanoanthracene (DCA) at the singlet excited state.…”
Section: Visible Light and Photoredox-catalyzed Functionalizationmentioning
confidence: 99%
“…In 2015, Pandey's group reported a conceptually new and synthetically valuable cross dehydrogenative benzylic C(sp 3 )–H amination reaction by visible‐light photoredox catalysis, which employed DCA (9,10‐dicyanoanthracene, 169 ) as a visible‐light absorbing photoredox catalyst (Scheme ). This protocol has a broad substrate scope and high regioselectivity.…”
Section: C(sp3)‐h Functionalizationmentioning
confidence: 99%